Evaluation of the physical and mechanical properties of flexible resins under the influence of thermocycling - Goiato, Marcelo Coelho [UNESP]; Sônego, Mariana Vivela [UNESP]; Souza, Lucas Seraphim [UNESP]; Commar, Betina Chiarelo [UNESP]; Gennari-Filho, Humberto [UNESP]; da Silva, Emily Vivianne Freitas [UNESP]; De Caxias, Fernanda Pereira [UNESP]; Dos Santos, Daniela Micheline [UNESP] (JCDR Research and Publications, 2018)
Introduction: New materials are developed all the time to better suit the patients' needs, such as flexible injectable thermoplastic resins that provide more esthetics to patients using removable partial dentures. Aim: The objective of this study was to evaluate the color change, microhardness and flexural strength of an experimental flexible acrylic resin under the influence of thermocycling. Materials and Methods: This in vitro study was conducted in Aracatuba Dental School, UNESP University. Two types of samples were made, 30 in circular format (3×10 mm) for color and microhardness tests, and 60 in rectangular format (64×10×3.3 mm) for the flexural strength test. The samples were divided into three groups (n=10), one of the experimental flexible resin tested, one with a flexible resin already marketed (Sorriflex), and a control group of a conventional thermopolymerisable acrylic resin (Lucitone). After the preparation, color, microhardness and flexural strength readings were taken, initially and after 2000 thermocycling cycles. The obtained data was submitted to analysis of variance ANOVA and post-hoc Tukey’s test when necessary. Results: All resins presented a clinically acceptable color variation (ΔE), with no significant difference between resin type (p>0.05). There was a difference in the hardness of resins in ascending order (Sorriflex, experimental and Lucitone) and the hardness increased after thermocycling (p<0.05). For the flexural strength, the only difference was related to the type of resin, the acrylic resin presented higher value with respect to the thermoplastic resins. Conclusion: We conclude that the tested experimental resin has properties similar to those found in the market, presenting the advantage of greater surface hardness.
Keywords: Acrylic resin; Color; Hardness